SURADE TRADITIONAL MARKET MANAGEMENT IN IMPROVING THE QUALITY OF COMFORT FOR THE COMMUNITY IN SUKABUMI DISTRICT - Agung Gumilang; Dian Purwanti; Tuah Nur (DIA: Jurnal Administrasi Publik, 2023)
Surade Traditional Market Management in Improving the Quality of Convenience for the Community in Sukabumi Regency. The purpose of this study is to identify and describe the management of the Surade traditional market and the inhibiting factors in its implementation. This is motivated by the problem of lack of facilities and infrastructure and the lack of optimal supervision by Surade Traditional Market officers on performance in market management. This research uses qualitative method and case study approach. Informants in this study were Surade Traditional Market Unit, Department of Industry and Trade of Sukabumi Regency, Traders in Surade traditional market, and the community as consumers. The validity of the data in this study used the method of source triangulation, technique triangulation, and member checking. The results showed that the management of the Sukabumi Regency Traditional Market had not been running well, as seen from the management of less than optimal cleaning facilities, the lack of firmness of the market manager against unruly traders, and the parking management managed by a third party had not gone well. While the inhibiting factor in the Management of Surade Traditional Market in its implementation is the absence of a budget for repairing facilities and infrastructure because it is still in a Covid-19 condition.